American Red Cross first aid responding to emergencies.
First aid-responding to emergencies, fourth edition is the definitive text from which many schools teach first aid, CPR and AED skills. Through an integrated teaching approach using classroom lecture, simulated emergency situations, discussion and hands-on skill practice, The American Red Cross offers instructors and students the vital skills needed to save a life.